The Size of Anterior Fontanelle and Its Determinants at Birth Among Neonates in Northern Ethiopia: A Cross-Sectional Study - Woldeyes, Dawit Habte (Pediatric Health Med Ther, 2020)
BACKGROUND: Fontanels are anatomical features of the infant human skull comprising any of the soft membranous gaps between the cranial bones that make up the calvaria of a neonate. Various factors are taught to be responsible for the differences in the size of the fontanel at birth. Accordingly, this study is performed to examine the size of the anterior fontanel, associated factors, and the clinical significance in Northern Ethiopia at birth. METHODS AND MATERIALS: A Cross-sectional study was conducted in a sample of 425 neonates. The data were analyzed using SPSS version 21. Descriptive and summary statistics were presented in the form of tables and figures. All the data were presented as mean ± S.D. The association between dependent variables and independent variables was explored by using Pearson’s chi-square test and logistic regressions. P-values <0.05 were considered to be statistically significant. RESULTS: The mean anterior fontanel size for the study population was 3.07 cm with a 95% confidence interval (3.00, 3.14). For a unit increase of head circumference of a neonate, the odds of having abnormal fontanel increase by 52.6%. Term neonates were 74.4% less likely to have abnormal fontanel size than preterm. Vaginally delivered neonates were 64.2% less likely to have abnormal fontanel size than neonates born by caesarean section. Low birth weight neonates were at risk of abnormal fontanel size. The odds ratio of the normal weight of neonate at birth was 0.327473 [95%, CI, (0.153364, 0.6992422)]. CONCLUSION: Gestational age, mode of delivery, head circumference, and birth weight are the most important determinant factors associated with anterior fontanel size.